Is Dorso-Volar Kinesiotape Added to the Home Exercise Program Effective in the Treatment of Carpal Tunnel Syndrome? Randomized Controlled Electrodiagnostic Study - Zincir Ercin, Dilek Ozge; Ozlu, Aysun; Cihan, Emine (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2024)
Objective We aimed to compare the short- and medium-term efficacy of dorso-volar kinesiotape (KT) added to home exercises (HE) with sham-KT and HE alone in the treatment of mild or moderate carpal tunnel syndrome (CTS) in terms of pain, symptom severity, function, gripping strength, and electrophysiological parameters.Materials and Methods A total of 120 patients (99 females, 21 males) were divided into three groups dorso-volar KT and HE (n=40), sham-KT and HE (n=40), and HE (n=40). Pain (The visual analog scale [VAS]), symptom severity (Boston symptom severity scale [SSS]), functional status (Boston functional status scale [FSS]), nerve conduction study (NCS), hand, finger muscle strength were evaluated pretreatment, at the end of treatment (4th week), and in the third month posttreatment.Results There were statistically significant improvements in VAS (p<0.001), Boston SSS (except HE group) (p<0.001), and Boston FSS (p<0.001) in all groups posttreatment compared to pretreatment, and more in the dorso-volar KT group than pretreatment and the posivite improvement continued at a decreasing rate in the third month posttreatment. At the end of treatment the dorso-volar KT group showed statistically significant improvement in Boston SSS (p<0.001, p<0.001) and Boston FSS (p<0.001, p<0.001) compared to the sham-KT and HE groups. Conclusions The combination of dorso-volar KT and HE program makes a more effective and durable contribution to the improvement of CTS symptom severity, pain and functional status, as well as handgrip strength and NCS parameters compared with sham-KT and HE program.
Keywords: Electromyography; Muscle strength; Pain; Kinesiotape; Carpal tunnel syndrome